2022
DOI: 10.1080/17482631.2022.2066254
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability, loss, and coping experiences of health care workers and first responders during the covid-19 pandemic: a qualitative study

Abstract: INTRODUCTION. The ongoing COVID-19 pandemic substantially affects health care workers from multiple disciplines, including nurses, physicians, therapists, and first responders. The aims of this study were to 1) explore and describe the experiences of health care workers and first responders working with individuals with COVID-19 infection, and 2) identify the support and strategies that were helpful during their experience.METHODS. A qualitative descriptive study was conducted via online video interviews of 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 45 publications
(69 reference statements)
7
17
0
Order By: Relevance
“…This resulted in anger as well as disappointment among nurses. These findings are similar to those reported by Bennett et al ( 2020 ), Moradi et al ( 2021 ), and Smeltzer et al ( 2022 ). The psychological toll from caring for patients during the pandemic was characterized by feelings of anxiety, distress, sadness, grief, and fear (Mental Health America, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This resulted in anger as well as disappointment among nurses. These findings are similar to those reported by Bennett et al ( 2020 ), Moradi et al ( 2021 ), and Smeltzer et al ( 2022 ). The psychological toll from caring for patients during the pandemic was characterized by feelings of anxiety, distress, sadness, grief, and fear (Mental Health America, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Some study participants were socially isolated by members of their communities who looked upon healthcare workers with disdain, further increasing their stress and anxiety (Hooper, 2021 ). Similar responses were reported by Robinson and Stinson ( 2021 ), Gordon et al ( 2021 ), and Smeltzer et al ( 2022 ), all of whom indicated that nurses in their studies wanted to educate the public and individuals in the community who failed to understand the severity of the pandemic.…”
Section: Discussionsupporting
confidence: 67%
“…Fatigue also caused negligence in safety measures to control infection, which significantly reduced patient care [ 31 ] and even threatened the patients’ as well as nurses’ health causing them to eventually contract the disease [ 27 ]. This finding also confirmed other studies’ results [ 26 , 27 ]. Based on these results, it seems that the physical and psychological distress inflicted on home care nurses during a pandemic must be regularly checked in order to prevent the consequences [ 32 ].…”
Section: Discussionsupporting
confidence: 94%
“…This support showed itself in titles such as “health care heroes” and “health care warriors” which were given to the health care staff. Unlike home care nurses in Iran, their counterparts in other countries [ 26 ] and in hospitals in Iran [ 27 ] didn’t discontinue their jobs at the beginning and continued looking after patients into the pandemic. This study indicates that these nurses lacked adequate training and preparation to face a crisis; therefore, they stepped away from fulfilling their duties due to the fear of contracting the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation